Total Quality Management Application on Services Quality at The Information and Complaints Service of Directorate General of Taxation - Eko Suwarno; Muhammad Sabil Muttaqin; Titiek Puspitasari (Future Science, 2020)
Changing environment and increasing community demands encourage Public Sector Organizations to begin to focus on the community and its services. However, the majority of Public Sector Organizations are considered slow in improving their services. This service sector is considered far behind compared to services in the private sector. Therefore, the fastest way to be able to match or even goes beyond is to implement systems and governance of private sector organizations to the public sector. One of the “tools” for the private sector that has been successfully applied in improving the performance of the public sector in different countries is “Total Quality Management”. Total Quality Management (TQM) is the philosophy that requires behavior change at every level of the organization to achieve competitive advantage by being customer-oriented. This study aims to examine the application of TQM on service quality at the information and complaint service office of the Directorate General of Taxation. The type of research that used in this paper is qualitative data. The result of the study found that quality is the main factor in service organization services. Total Quality Management has been implemented effectively at the information and complaint service office of the Directorate General of Taxation.